Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №61

Упростите выражение:
а)
$\frac{x}{y - 1} + \frac{5}{1 - y}$
;
б)
$\frac{a}{c - 3} - \frac{6}{3 - c}$
;
в)
$\frac{2m}{m - n} + \frac{2n}{n - m}$
;
г)
$\frac{5p}{2q - p} + \frac{10q}{p - 2q}$
;
д)
$\frac{a^2 + 16}{a - 4} + \frac{8a}{4 - a}$
;
е)
$\frac{x^2 + 9y^2}{x - 3y} + \frac{6xy}{3y - x}$
.

Решение а

$\frac{x}{y - 1} + \frac{5}{1 - y} = \frac{x}{y - 1} - \frac{5}{y - 1} = \frac{x - 5}{y - 1}$

Решение б

$\frac{a}{c - 3} - \frac{6}{3 - c} = \frac{a}{c - 3} + \frac{6}{c - 3} = \frac{a + 6}{c - 3}$

Решение в

$\frac{2m}{m - n} + \frac{2n}{n - m} = \frac{2m}{m - n} - \frac{2n}{m - n} = \frac{2m - 2n}{m - n} = \frac{2(m - n)}{m - n} = 2$

Решение г

$\frac{5p}{2q - p} + \frac{10q}{p - 2q} = \frac{5p}{2q - p} - \frac{10q}{2q - p} = \frac{5p - 10q}{2q - p} = \frac{5(p - 2q)}{2q - p} = -\frac{5(p - 2q)}{p - 2q} = -5$

Решение д

$\frac{a^2 + 16}{a - 4} + \frac{8a}{4 - a} = \frac{a^2 + 16}{a - 4} - \frac{8a}{a - 4} = \frac{a^2 - 8a + 16}{a - 4} = \frac{(a - 4)^2}{a - 4} = a - 4$

Решение е

$\frac{x^2 + 9y^2}{x - 3y} + \frac{6xy}{3y - x} = \frac{x^2 + 9y^2}{x - 3y} - \frac{6xy}{x - 3y} = \frac{x^2 - 6xy + 9y^2}{x - 3y} = \frac{(x - 3y)^2}{x - 3y} = x - 3y$